Perplexity and Knowledge - Clark, M. author. aut Link
VIII, 246 p.
Keywords: In making his distinction between revisionary and descriptive metaphysics, P.F. Strawson wrote that the former has some value provided that its "partial vision" is at the service of the latter, "which needs no justification at all beyond that of inquiry in general." (Individuals, p. 9) Perhaps we feel no need to ask what justification there is for inquiry in general. But if we do recognize any such need, then we discover that inquiry is self-justifying. The more I put it into question, the more I bring the theme of my inquiry to light in my performance of inquiring. Questioning is the business of philosophers. They are now content to leave the search for detailed information to experts in the various disciplines that have won their independence from philosophy. The questioning a philosopher conducts is of the 'second-order'. He asks about the status of various sorts of questions, the types of knowledge they yield and of con fusion into which they lead.